PERAN PEREMPUAN DALAM LEMBAGA TUHA PEUT SEBAGAI LEMBAGA ADAT ACEH DAN PEMERINTAHAN GAMPONG - Fauzi Abubakar (IAIN Ponorogo, 2015)
Abstract: This study was aimed at assessing the role of women in the discourse of feminism which was not only in the form theoretical talks and debates but also practical ones in various parts of the world, including in Aceh, Indonesia. In practical level, the role of women had played in various institutions such as in traditional/conventional institutions and government ones. The focus of the problem was how the role of women in traditional institutions 'Tuha Peut' and the local government of Aceh were. Through a historical approach, this paper tried to explore the role of women in traditional institutions 'Tuha Peut' and local government in Aceh. Based on the various data collected such as observation, interviews and documentation, it showed that the role of women in institutions of Tuha Peut, as a traditional institution of Aceh and a government administrator of Gampong Aceh, was equal to the role of men, especially in formulating policies in Gampong. Data also showed that women had more prominent role, especially in efforts to achieve policies on the equity of gender. Acehnese women could not only give advice and consideration to Keuchik (head of the alliance of indigenous peoples of Gampong) but also could give supervision to the Reusam Gampong. Women also could become a mediator to resolve the conflicts that arised in Aceh through the consultation of indigenous peoples and offering a solution for the sake of ending the conflict properly without taking the formal and official legal justice.الملخص :أصبح دور المرأة – في فكرة النسوية – حديثا ليس فقط نظريا بل تطبيقيا في كثير من أنحاء العالم ومنها في أتشيه، إندونيسيا. وفي التطبيق، كان دور المرأة في شتّى المؤسسات، مؤسسة عادة أو حكومة. كان تركيز المسألة في هذه الدراسة هي كيف يكون دور المرأة في مؤسسة العادة